2019
DOI: 10.1103/physrevphyseducres.15.020102
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase study examining perspectives and use of quantitative methods in physics education research

Abstract: While other fields such as statistics and education have examined various issues with quantitative work, few studies in physics education research (PER) have done so. We conducted a two-phase study to identify and to understand the extent of these issues in quantitative PER . During Phase 1, we conducted a focus group of three experts in this area, followed by six interviews. Subsequent interviews refined our plan. Both the focus group and interviews revealed issues regarding the lack of details in sample desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Some examples include sample size, the number of features, the number of numerical features, the number of categorical features, and the percentage of observation of the majority class or outcome balance (Couronné et al, 2018). Just as there have been calls for increased reporting of demographics in the DBER and EDM communities to understand how results might depend on the sample population or generalize (Kanim and Cid, 2020;Paquette et al, 2020), we are calling for the same with the explanatory and predictive models we create, partially addressing some of the questions raised by Knaub et al (2019) in their analysis of physics education research quantitative work. By doing so, we hope for greater acknowledgement of possible sources of bias or false negatives in feature selection as a result of the data or algorithms used in DBER and EDM studies.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Some examples include sample size, the number of features, the number of numerical features, the number of categorical features, and the percentage of observation of the majority class or outcome balance (Couronné et al, 2018). Just as there have been calls for increased reporting of demographics in the DBER and EDM communities to understand how results might depend on the sample population or generalize (Kanim and Cid, 2020;Paquette et al, 2020), we are calling for the same with the explanatory and predictive models we create, partially addressing some of the questions raised by Knaub et al (2019) in their analysis of physics education research quantitative work. By doing so, we hope for greater acknowledgement of possible sources of bias or false negatives in feature selection as a result of the data or algorithms used in DBER and EDM studies.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Finally, communication of data context has also been observed to be an issue in PER. Knaub et al [32] found that approximately half of papers published in Physical Review: PER do not describe basic descriptive information about the students being studied such as their demographics, average grades, or institutional descriptors [33].…”
Section: Data Collectionmentioning
confidence: 99%
“…It also means discussing how the data was collected (e.g., in-class, online, for credit, optional, etc.). We recommend following the questions presented in Knaub et al [32] such as "what information regarding the sample is useful for the audience," as well as emphasizing explicit sample descriptions and limitations [33].…”
Section: A Raw Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This Focused Collection offers the PER community with a variety of ideas to support and strengthen the work that we conduct. A number of authors pushed on our ideas of data and analysis providing an opportunity for an ongoing conversation about what researchers need to consider when designing, executing, and reporting a quantitative study [11][12][13][14]. Other authors highlighted analytical approaches that push the boundaries of quantitative PER or that solve persistent and common issues in our analyses [15][16][17][18][19].…”
mentioning
confidence: 99%